2020
DOI: 10.3390/ijms21103581
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines Expression and Effects in Oocyte Maturation, Fertilization and Early Embryo Development: Lessons from Mammals and Birds

Abstract: Some evidence shows that body mass index in humans and extreme weights in animal models, including avian species, are associated with low in vitro fertilization, bad oocyte quality, and embryo development failures. Adipokines are hormones mainly produced and released by white adipose tissue. They play a key role in the regulation of energy metabolism. However, they are also involved in many other physiological processes including reproductive functions. Indeed, leptin and adiponectin, the most studied adipokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 182 publications
0
14
0
4
Order By: Relevance
“…However, the detailed mechanism remains to be elucidated in the future. Poultry ovaries cannot form a corpus luteum after ovulation, poultry P4 is mainly produced by follicular GCs ( Yang et al., 2005 ), and poultry follicles also have the ability to secrete P4 after ovulation ( Estienne et al., 2020 ). Studies have shown that low levels of P4 can mediate an increase in low-frequency LH pulses, prolonging the duration of the dominant follicles and thus affecting the maturation and quality of oocytes ( Savio et al., 1993 ), while high levels of P4 can inhibit the synthesis of luteinizing hormone and ultimately cause atresia of the dominant follicles ( Gu and Zhao, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanism remains to be elucidated in the future. Poultry ovaries cannot form a corpus luteum after ovulation, poultry P4 is mainly produced by follicular GCs ( Yang et al., 2005 ), and poultry follicles also have the ability to secrete P4 after ovulation ( Estienne et al., 2020 ). Studies have shown that low levels of P4 can mediate an increase in low-frequency LH pulses, prolonging the duration of the dominant follicles and thus affecting the maturation and quality of oocytes ( Savio et al., 1993 ), while high levels of P4 can inhibit the synthesis of luteinizing hormone and ultimately cause atresia of the dominant follicles ( Gu and Zhao, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, it was di cult to achieve a high dose of plasma VC content through dietary VC supplementation [15,31]. The follicle maturation process is accompanied by the deposition of lipids [35], which is not bene t for VC deposition, and it only takes 1.5 h to complete albumen formation in magnum [13], which leads a very short window time provided for VC deposition. In addition, limited increase in SVCT1 expression induced by dietary VC supplementation may make it di cult to activate the secretion of ovary and magnum, so dietary VC supplementation failed to increase VC deposition in produced eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Egg yolk and albumen are formed at hen's ovary and magnum, respectively [13,14]. So, if VC could be deposited in yolk and albumen of produced eggs, it would be inseparable from the transportation and secretion function in hen's ovary and magnum.…”
Section: Introductionmentioning
confidence: 99%
“…Adipokines have, from being considered endocrine regulators of energy metabolism and secreted by white adipose tissue, evolved as involved in fertility regulation, perhaps acting as metabolic sensors [ 121 ]. Leptin and adiponectin are now accompanied by the novel adipokines resistin, chemerin, apelin and visfatin, which, alongside cognate receptors, are now evidently expressed in the reproductive tissues of human and animals, including the testis [ 121 ], and affect various reproductive events [ 122 ]; their disarray or absence can also cause infertility [ 123 ]. Being produced by the testis or incoming into the male genital tract, they have been identified in SP in humans and animals, including the pig [ 124 , 125 ], and they attach via specific receptors to the sperm plasmalemma [ 126 ].…”
Section: The Composition Of the Seminal Plasma: Comparative Aspectsmentioning
confidence: 99%